The Gas Transfer through Polar Sea ice experiment: Insights into the rates and pathways that determine geochemical fluxes. Issue 12 (19th December 2015) - Lovely, A.; Loose, B.; Schlosser, P.; McGillis, W.; Zappa, C.; Perovich, D.; Brown, S.; Morell, T.; Hsueh, D.; Friedrich, R.
Abstract: Sea ice is a defining feature of the polar marine environment. It is a critical domain for marine biota and it regulates ocean‐atmosphere exchange, including the exchange of greenhouse gases such as CO2 and CH4 . In this study, we determined the rates and pathways that govern gas transport through a mixed sea ice cover. N2 O, SF6, 3 He, 4 He, and Ne were used as gas tracers of the exchange processes that take place at the ice‐water and air‐water interfaces in a laboratory sea ice experiment. Observation of the changes in gas concentrations during freezing revealed that He is indeed more soluble in ice than in water; Ne is less soluble in ice, and the larger gases (N2 O and SF6 ) are mostly excluded during the freezing process. Model estimates of gas diffusion through ice were calibrated using measurements of bulk gas content in ice cores, yielding gas transfer velocity through ice ( k ice ) of ∼5 × 10 −4 m d −1 . In comparison, the effective air‐sea gas transfer velocities ( keff ) ranged up to 0.33 m d −1 providing further evidence that very little mixed‐layer ventilation takes place via gas diffusion through columnar sea ice. However, this ventilation is distinct from air‐ice gas fluxes driven by sea ice biogeochemistry. The magnitude of keff showed a clear increasing trend with wind speed and current velocity beneath the ice, as well as the combination of the two. This result indicates that gas transfer cannot be uniquely predicted by wind speed alone in the presence of sea ice. Key Points: Gas diffusion through sea ice is slower than molecular diffusion in water Helium solubility in ice is greater than in water Air‐sea gas exchange is driven by currents as well as wind in the sea ice zone